The Effectiveness of Strength Based Intervention Motivational interviewing Group Counseling to Improve Students’ Self Compassion - Azizah, Nurul; Wibowo, Mungin Eddy; Purwanto, Edy (Jurnal Bimbingan Konseling)
This study aimed to analyze the effectiveness of strength based intervention motivational interviewing group counseling to improve students? self-compassion. The study used pretest and multiple posttest design. Purposive sampling was used to select 14 experimental subjects which were grouped into two in random or in other words, 7 people for each group. For more, the data collection technique in this study used self-compassion scale-short form (SCS-SF). The results of mixed repeated measures ANOVA showed that strength based intervention motivational interviewing group counseling was effective to improve self-compassion (F (1.12) = 365.97, p < 0.05). This also could be seen in the effect of time (F (2,24) = 424.98, p < 0.05), and interaction effect between time and group (F (2,24) = 581.59, p < 0.05). These findings assert that strength based intervention motivational interviewing group counseling is effective to improve students? self-compassion.